Progression of plastic strain on heavy-haul railway rail under random pure rolling and its influence on crack initiation. (October 2018) - Reis, Thairon; Lima, Eduardo de Abreu; Bertelli, Felipe; dos Santos Junior, Auteliano Antunes
Highlights: Plastic strain in rails stabilizes after a few load cycles for heavy-haul railroads, considering pure rolling. Life to shelling initiation in rails can be estimated using multiaxial high cycle fatigue after plastic strain stabilization. Coupling analytical and numerical tools were effective to evaluate successive loading in rails, reducing time and keeping the accuracy. The number of cycles until failure initialization is quite the same for any position of the contact on the rail, about hundred thousand of cycles. Abstract: The present work evaluates the plastic strain accumulation on railway rails for heavy-haul transportation and the effect of them on the life cycle and the stress-strain responses considering random loading passes of normal loads on the top of rail for wheel-rail pure rolling conditions. The normal pressure distribution on the contact region was estimated by the Hertz theory and applied on the surface of the rail in a tridimensional elastoplastic finite element model. Multiaxial Dang Van criterion was applied to estimate the life to crack nucleation. The results show that the level of plastic accumulation presents distinct magnitudes depending on the position analyzed, reaching similar plastic accumulation in analogous positions on the subsurface after several passes, for two different starting positions. That result is fundamental for life analyses, since indicates that, no matter the starting point, the computed life cycles always stabilizes after a few number of cycles. From that, the fatigue life to shelling can be estimated using high cycle models.